Results of new-generation balloon vs. self-expandable transcatheter heart valves for bicuspid aortic valve stenosis - Deutsch, Oliver; Vitanova, Keti; Ruge, Hendrik; Erlebach, Magdalena; Krane, Markus; Lange, Rüdiger (Frontiers in Cardiovascular Medicine, 2023)
Data comparing new-generation self-expandable (SEV, Evolut R/PRO) versus balloon-expandable (BEV, SAPIEN 3/3Ultra) transcatheter heart valve replacement (TAVR) in bicuspid aortic valve stenosis (BAV) is limited. Our aim was to compare 30-day results of SEV and BEV implantations in patients with BAV.A total of 2009 patients underwent TAVR between April 2015 and June 2021 at our Centre. From our institutional registry, we identified 106 consecutive patients with BAV who underwent TAVR using SEV and BEV.A 106 patients (n=68 BEV; n=38 SEV) were included. Mean age was 74.6±8.8 years (BEV) vs.75.3±8.7 years (SEV) (p=0.670) and Society of Thoracic Surgeons score was 2.6±1.9 (BEV) vs. 2.6±1.6 (SEV) (p=0.374), respectively. Device landing zone calcium volume (DLZ-CV) was 1168±811 vs. 945±850 mm3 (p=0.192). Valve Academic Research Consortium (VARC)-3 device success at 30 days was similar (BEV 80.9% vs. SEV 86.8%; p=0.433). More post-dilatations were performed in SEVs (23.5% BEV vs. 52.6% SEV; p=0.002). Overall mean gradient at 30 days followup was 11.9±4.6 mmHG (BEV) vs. 9.2±3.0 mmHG (SEV) (p=0.002). A mild-moderate degree of paravalvular leak (PVL) was detected more often in the SEV group (7.4% vs. 13.2%; p=0.305). A trend towards higher rate of permanent pacemaker implantation was observed in SEV (11.8% vs. 23.7%; p=0.109). This is a provisional file, not the final typeset articleTreatment of BAV revealed similar performance using BEV and SEV. In this retrospective cohort study, hemodynamics were more favorable with the SEV, although there was a trend toward more PVL and significantly more post-dilations. Values are mean ± SD or n (%). AKIN = Acute Kidney Injury Network, EOA = effective orifice area, iEOA = indexed effective orifice area, LVEF = left ventricular ejection fraction, TIA = transient ischemic attack.